Common Mental Health Disorders and Mental Health Help-Seeking Behaviors among Caregivers of Diabetic Children in Ismailia - Shaimaa L. Lotfy; Amany H. Refaat; Shaimaa A. Amer; Sally F. Elotla (Journal of High Institute of Public Health, 2022)
Background: Mental health issues are major public health concern. Primary caregivers of diabetic children carry multi-dimensional burden during management of this chronic condition and are vulnerable to various mental disorders. Objective(s): To identify the common mental health disorders and mental health help-seeking behaviors among caregivers of diabetic children. Methods: A comparative cross-sectional study including primary caregivers of children with type-1 diabetes (n=151) and caregivers of non-diabetic children (n=151) was carried out at Suez Canal University and Health Insurance hospitals in Ismailia, Egypt. Participants completed a structured questionnaire including socio-demographic characteristics, medical histories, and recent mental health help-seeking behaviors. WHO self-reporting questionnaire-20 (SRQ-20) was used to assess the suspected Common Mental Health Disorders (CMHD) among studied caregivers. Results: suspected CMHD among caregivers of diabetic children was relatively higher than the caregivers of non-diabetic children (75.5% vs. 72.2%, p = 0.513). The proportion of caregivers of diabetic children who sought formal sources of mental health help was significantly lower than caregivers of non-diabetic children (6.7% vs. 20.5%). Caregivers with suspected CMHD had significantly lower perceived mental and physical health and sought mental health help more than those with no suspected CMHD (31.8% vs. 17.7%, p =0.02). The main significant determinants of suspected CMHD were the perceived mental and physical health (p < 0.001, and 0.027, respectively). Conclusion: No significant difference in CMHD existed between caregivers in studied groups. Caregivers of diabetic children were less likely to seek formal sources of mental health help-seeking. Perceived mental and physical health were the determinants of CMHD.